Detection of Borrelia persica Infection in Ornithodoros Tholo¬Zani Using PCR Targeting RRS Gene and Xenodiagnosis - F Mohtarami; T Satvat; N Piazak; MA Oshaghi; N Choubdar; J Rafinejad; A Barmaki (Iranian Journal of Public Health, 2011)
Background: Relapsing fever caused by Borrelia persica, is an acute tick-borne disease which is transmitted by soft ticks of Ornithodoros tholozani to human.Methods: Value of PCR and xenodiagnosis for detection of B. persica in O. tholozani ticks was compared. Sixty-four Borrelia-free ticks were fed on infected guinea pigs and used for the experiments. For xenodiagnosis, a group of 32 ticks in subsequent blood meal were fed on sterile guinea pigs and the indication of B. persica in the animal blood was tested 5-14 days later by dark-field microscopy. For PCR, all 64 ticks were subjected to PCR against B. persica rrs gene (16S-rDNA). Also sensitivity of PCR in terms of minimum detectable number of spirochetes as well as the effects of tick sex and post digestion was tested.Results: PCR revealed B.persica DNA in 98.4% ticks, in which B. persica were found in 25.0% by xenodiagnosis. PCR was enough sensitive to give positive results for DNA of 1 spirochete. PCR success rates were similar for male or female ticks. Course of time did not affect the efficacy of PCR and similar results were observed for ticks of immediately fed, semi- or completely gravid or completely digested blood ones.Conclusion: Our results indicate that due to very low specificity and time consuming, xenodiagnosis is not a useful method whereas PCR method has advantages for study the Borrelia prevalence in ticks.